Estimation of incubation period and generation time of COVID-19 under length-biased sampling and interval censoring - Nakhaeirad, Najmeh (University of Pretoria, 2025)
Mini Dissertation (MSc (Advanced Data Analytics))--University of Pretoria, 2025.